2014
DOI: 10.1523/jneurosci.2768-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Representation and Distribution of Visual Information by Specific Cell Types in Mouse Superficial Superior Colliculus

Abstract: The superficial superior colliculus (sSC) occupies a critical node in the mammalian visual system; it is one of two major retinorecipient areas, receives visual cortical input, and innervates visual thalamocortical circuits. Nonetheless, the contribution of sSC neurons to downstream neural activity and visually guided behavior is unknown and frequently neglected. Here we identified the visual stimuli to which specific classes of sSC neurons respond, the downstream regions they target, and transgenic mice enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
334
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(409 citation statements)
references
References 61 publications
24
334
3
1
Order By: Relevance
“…Sparse projections could also be detected in the dLGN (Fig. 3E), as described previously (Gale and Murphy, 2014). Together, these experiments demonstrate that a small population of TG cells are GABAergic and sparsely innervate the dLGN.…”
Section: The Vast Majority Of Tectogeniculate Projections Are Non-gabsupporting
confidence: 88%
See 4 more Smart Citations
“…Sparse projections could also be detected in the dLGN (Fig. 3E), as described previously (Gale and Murphy, 2014). Together, these experiments demonstrate that a small population of TG cells are GABAergic and sparsely innervate the dLGN.…”
Section: The Vast Majority Of Tectogeniculate Projections Are Non-gabsupporting
confidence: 88%
“…A recent study of mouse NFV cells reported that all were direction selective (Gale and Murphy, 2014).…”
Section: Tectogeniculate Pathwaymentioning
confidence: 99%
See 3 more Smart Citations